Biodiesel Production Using Vegetable Oil and Animal Fat Mixtures - Sharif, Yousef; Akosman, Cevdet (My University, 2025)
In this study, the biodiesel samples were produced by using the mixtures of vegetable oils (sunflower and corn oils) and beef tallow. In the experiments, the mixtures of vegetable oils and beef tallow at different ratios were trans esterified in a batch-wise system with methanol by using sodium hydroxide as catalyst. The effects of temperature, time, amount of catalyst and vegetable oil/beef tallow ratio on biodiesel production were studied. The experiments were carried out by using amount of catalyst ranging from 0.125 to 1 wt% of feedstocks by keeping the molar ratio of 1/6 (oil to methanol) at temperatures between 40-70 °C for different times ranging from 25 to 80 min. The biodiesel from the mixture of vegetable oils and beef tallow were obtained using the blends containing 0, 5, 10 and 20% of beef tallow by volume. All experiments were conducted at a fixed mixing speed of 600 rpm. The biodiesel conversion increased sharply until 0.75 wt% catalyst amount and slightly between 0.75wt% and 1 wt% with increasing reaction time for all feed stocks. Biodiesel conversions increased with increasing temperature from 40 to 60°C, but there was no significant increase after this temperature. The degree of conversion decreased as the beef tallow content increased in the mixture. The values of density and kinematic viscosity of biodiesel samples increased with an increase of beef tallow amount in vegetable oils. On the other hand, the heat values of biodiesel were similar to sunflower oil and beef tallow from which they were produced.
Keywords: Biodiesel; animal fat; transesterification; vegetable oil